2019
DOI: 10.3747/co.26.4769
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Utility Analysis of 21-Gene Assay for Node-Positive Early Breast Cancer

Abstract: Background For women with lymph node (LN)–positive, estrogen receptor–positive, and her2 (human epidermal growth factor receptor 2)–negative breast cancer (BCa), current guidelines recommend treatment with both hormonal therapy and chemotherapy. The 21-gene Recurrence Score (RS) assay might be helpful in selecting patients with BCA who can be spared chemotherapy when they have 1–3 positive LNS and a lower risk of recurrence. In the present study, we performed a cost–utility analysis comparing use of the 21-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…However, the savings could actually be greater if the cost of managing short- and long-term toxicities were also considered, including febrile neutropenia, hospitalizations, congestive heart failure, leukemia, and neuropathy. 32-34 Furthermore, while we did not conduct a formal cost-effectiveness model analysis, when incorporating cumulative costs and quality-adjusted life years (QALY), other studies also determined the RS result to be a cost-effective tool. 35 , 36 It is important to note, however, that the selection of our patient cohort may have influenced the magnitude of cost reduction, which could have otherwise been less pronounced among all-comers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the savings could actually be greater if the cost of managing short- and long-term toxicities were also considered, including febrile neutropenia, hospitalizations, congestive heart failure, leukemia, and neuropathy. 32-34 Furthermore, while we did not conduct a formal cost-effectiveness model analysis, when incorporating cumulative costs and quality-adjusted life years (QALY), other studies also determined the RS result to be a cost-effective tool. 35 , 36 It is important to note, however, that the selection of our patient cohort may have influenced the magnitude of cost reduction, which could have otherwise been less pronounced among all-comers.…”
Section: Discussionmentioning
confidence: 99%
“…49 Studies which assumed a differential hazard ratio for distant recurrence between RS result subgroups concluded that the 21-gene assay was either dominant or considered to be cost-effective compared to using clinical-pathologic factors alone. 25,[50][51][52][53] Studies which assumed a constant reduction in the rate of distant recurrence with chemotherapy irrespective of RS result were less likely to conclude that the 21-gene assay is costeffective. 54,55 This is consistent with the findings from the prognostic-only scenario in the current analysis which reported an ICER considerably higher than the NICE WTP per QALY threshold, and the prognostic-only base case assumed in the NICE DAR prior to the publication of results from the TAILORx study, which demonstrated that chemotherapy does not provide additional benefit to patients with RS results 11-25.…”
Section: Comparison To Published Evidencementioning
confidence: 99%
“…In recent years, many researchers have been devoted to find and validate molecular alterations to serve as a prognostic and predictive biomarker. One of the validated and widely used multi-gene signature tests is the 21 genes, which is commonly applied for predicting the breast cancer outcomes [ 3 , 4 ]. In addition, there are also studies demonstrating that epigenetic alterations, such as promoter hypermethylation or hypomethylation, can lead to aberrant gene expression in tumor cells [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%